The Rise of Cafes in Waduk Cengklik: Exploring the Implication for Locals - Musthafa, Adel; Herawati, Gayatri Ajeng (Journal of Tourism and Creativity, 2024)
This research examines the rapid increase in the number of cafÃ©s around the Cengklik Reservoir and explores the implications for the local community. This research uses a qualitative survey method by collecting data from 10 interviews with local residents. The results showed some positive impacts for local residents. The findings show that although the proliferation of cafÃ©s has spurred local economic growth and created new jobs, it has also created some challenges such as the increased intensity of passing vehicles. The conclusion of this study is that the emergence of cafes around the Cengklik Reservoir has a positive impact on local residents covering three aspects: economic, environmental and socio-cultural.